Physicochemical characterization and differentiation of the components of the cutaneous basement membrane zone. - Allen, J; Schomberg, K; Wojnarowska, F (1997)
Many of the techniques used in the diagnosis and characterization of the acquired blistering diseases of the skin and of their target antigens require the use of tissue that has been modified by heat, chemicals, or by proteolytic digestion. The effect these treatments may have on the blistering disease antigens is poorly understood and has seldom been taken into account in the interpretation of the results. Likewise, their effect on the immunodetection and expression of the ubiquitous proteins of the basement membrane zone and extracellular matrix has rarely been investigated. We have addressed this problem by probing tissue split after heat, chemical treatment and proteolytic digestion with an extensive panel of antibodies to the hemidesmosome-plasma membrane-anchoring filament complex, the extracellular matrix and the anchoring fibrils. The results showed that chemical modification by sodium chloride, calcium chloride and ethylenediaminetetraacetic acid, and incubation in 0.15 mol/L NaCl at 56 degrees C for 1 min did not adversely affect the expression of the alpha 6 beta 4 integrin, laminin-5, the LH39 antigen, laminin-1, collagen type IV or collagen type VII. The methods that involved proteolytic digestion had the greatest detrimental effect on these basement membrane components, with pepsin having a damaging effect on the greatest number of antigens, and the LH39 antigen being the most sensitive to proteolytic degradation. This project has highlighted the susceptibility of the basement membrane zone and extracellular matrix proteins to proteolytic hydrolysis. It has demonstrated a way of differentiating between specific proteins, and has shown its potential for the differential diagnosis of the autoimmune blistering disease antigens.